Probing cosmic dawn: Ages and star formation histories of candidate z ≥ 9 galaxies. Issue 3 (24th June 2021) - Laporte, N; Meyer, R A; Ellis, R S; Robertson, B E; Chisholm, J; Roberts-Borsani, G W
ABSTRACT: We discuss the spectral energy distributions and physical properties of six galaxies whose photometric redshifts suggest they lie beyond a redshift z ≃ 9. Each was selected on account of a prominent excess seen in the Spitzer /IRAC 4.5 μ m band which, for a redshift above z = 9.0, likely indicates the presence of a rest-frame Balmer break and a stellar component that formed earlier than a redshift z ≃ 10. In addition to constraining the earlier star formation activity on the basis of fits using stellar population models with BAGPIPES, we have undertaken the necessary, but challenging, follow-up spectroscopy for each candidate using various combinations of Keck/MOSFIRE, VLT/X-shooter, Gemini/FLAMINGOS2, and ALMA. Based on either Lyman-α or [O iii ] 88 μ m emission, we determine a convincing redshift of z = 8.78 for GN-z-10-3 and a likely redshift of z = 9.28 for the lensed galaxy MACS0416-JD. For GN-z9-1, we conclude the case remains promising for a source beyond z ≃ 9. Together with earlier spectroscopic data for MACS1149-JD1, our analysis of this enlarged sample provides further support for a cosmic star formation history extending beyond redshifts z ≃ 10. We use our best-fitting stellar population models to reconstruct the past rest-frame UV luminosities of our sources and discuss the implications for tracing earlier progenitors of such systems with the James Webb Space Telescope .